The complete mitochondrial genome of Parabotia fasciata (Cypriniformes: Cobitidae). (3rd May 2016) - Wei, Min; Yu, Peng; Yang, Yingming; Wan, Quan
Abstract: Parabotia fasciata is a small-sized benthopelagic fish species in the family Cobitidae. In the present study, we reported the complete mitochondrial genome of P fasciata . The complete mitochondrial genome of P. fasciata was 16, 590 bp in length, which contained 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, a control region, and an L-strand replication origin (OL ). Besides, its overall nucleotide base composition of mitogenome was 31.28% for A, 25.83% for T, 15.72% for G and 27.17% for C, as well as an AT content of 57.11%.